Policing and media public relations, simulations and communications - Lee, Murray 1965-; McGovern, Alyce (London Routledge, Taylor & Francis Group, 2014)
"This book examines the relationship between police, media and the public and analyses the shifting techniques and technologies through which they communicate. In a critical discussion of contemporary and emerging modes of mediatized police work, Lee and McGovern demonstrate how the police engage with the public through a fluid and quickly expanding assemblage of communications and information technologies.Policing and Media explores the rationalities that are driving police/media relations and asks; how these relationships differ (or not) from the ways they have operated historically; what new technologies are influencing and being deployed by policing organizations and police public relations professionals and why; how operational policing is shaping and being shaped by new technologies of communication; and what forms of resistance are evident to the manufacture of preferred images of police. The authors suggest that new forms of simulated and hyper real policing using platforms such as social media and reality television are increasingly positioning police organisations as media organisations, and in some cases enabling police to bypass the traditional media altogether. The book is informed by empirical research spanning 10 years in this field and includes chapters on journalism and police, policing and social media, policing and reality television, and policing resistances. It will be of interest to those researching and teaching in the fields of Criminology, Policing and Media as well as police and media professionals"-- Provided by publisher.
Locating police media public relations -- The logics of police media work -- "Simulated policing" : framing contemporary police media work -- Policing the press release -- Policing social media -- Policing reality television -- New technologies and struggles of representation -- Resistances and old media -- Conclusion -- Appendix: Research methods.
Includes bibliographical references (pages 223-241) and index.
Keywords: Police-community relations; Community policing; Police and mass media; Information technology